Tan Wah Piow, smokescreens & mirrors: tracing the “Marxist Conspiracy.” Singapore: Function 8 limited, 2012 - Hossain, Ishtiaq (International Islamic University Malaysia, 2013)
Review examines the so-called Marxist Conspiracy in Singapore in the 1980s.